Health and public policy determinants: selection of indicators for health problems. (Colombia Medica, 2007)
Introduction: Health planning requires information from all sectors, usually available, but not used frequently. Information systems in Health appeared more than 3 decades ago but decisions are usually taken on considerations directed to the solution of a manifestation without modification of causal factors. The purpose of this study was to evaluate the usefulness of available data to identify population groups with similar characteristics associated to health problems and to identify simple markers to serve as a basis for decisions directed to solve them. Methods: Ecological study. Data were identified, collected and collated from public institutions and from recent studies for analysis. Association and correlation among the different variables identified those with the capacity to discriminate population groups. Household socio economic stratum had a significant association with most variables and was used to divide «Barrios» in four conglomerates. Results: Lower conglomerates presented deficiencies in household and education, larger proportion of young population, lower mean death age, higher mortality caused by accidents and violence, and lower stature. Middle and higher income conglomerates had better household conditions and the principal cause of death was tumors and chronic diseases. Public services were similar for all except telephone. Weighed household stratum by neighborhood «barrio» explained more that 80% of variance for most variables. It is proposed that this marker, available and easy to obtain, the instrument to define local development plans with periodic validations to evaluate its capacity.